2017
DOI: 10.1186/s13041-017-0319-6
|View full text |Cite
|
Sign up to set email alerts
|

Genetic deletion of mGlu2 metabotropic glutamate receptors improves the short-term outcome of cerebral transient focal ischemia

Abstract: We have recently shown that pharmacological blockade of mGlu2 metabotropic glutamate receptors protects vulnerable neurons in the 4-vessel occlusion model of transient global ischemia, whereas receptor activation amplifies neuronal death. This raised the possibility that endogenous activation of mGlu2 receptors contributes to the pathophysiology of ischemic neuronal damage. Here, we examined this possibility using two models of transient focal ischemia: (i) the monofilament model of middle cerebral artery occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 34 publications
(39 reference statements)
3
11
0
Order By: Relevance
“…Using the four-vessel occlusion model of transient global ischemia in rats, we have shown that selective pharmacological activation of mGlu2 receptors amplified hippocampal damage, whereas mGlu2 receptor blockade was neuroprotective (19). Similar findings were obtained using mice lacking mGlu2 receptors, in which the infarct size was enhanced in response to transient focal ischemia (20). To our knowledge, there are no studies on mGlu3 receptors and brain ischemia, although the selective activation of mGlu3 receptors was shown to be neuroprotective in in vitro studies (17,(21)(22)(23)(24).…”
Section: Introductionsupporting
confidence: 69%
See 1 more Smart Citation
“…Using the four-vessel occlusion model of transient global ischemia in rats, we have shown that selective pharmacological activation of mGlu2 receptors amplified hippocampal damage, whereas mGlu2 receptor blockade was neuroprotective (19). Similar findings were obtained using mice lacking mGlu2 receptors, in which the infarct size was enhanced in response to transient focal ischemia (20). To our knowledge, there are no studies on mGlu3 receptors and brain ischemia, although the selective activation of mGlu3 receptors was shown to be neuroprotective in in vitro studies (17,(21)(22)(23)(24).…”
Section: Introductionsupporting
confidence: 69%
“…The infarct area was outlined at a magnification of ×2.5, and it was quantified using Scion Image software (NIH, Bethesda, MD, USA). Then, the volume was calculated by integrating the cross-sectional area of damage on each stained section and the distance between them (20,30).…”
Section: Histologymentioning
confidence: 99%
“…Suboptimal neuroprotective effects of orthosteric mGlu2/3 receptor agonists have been observed in animal models of global and focal brain ischemia ( Bond et al, 1998 ; Bond et al, 2000 ), probably due to the involvement of mGlu2 receptors expressed in neurons ( Corti et al, 2007 ; Motolese et al, 2015 ; Mastroiacovo et al, 2017 ). However, the role of microglial mGlu2 receptor in stroke ischemia has not been fully elucidated.…”
Section: Group II Mglu Receptorsmentioning
confidence: 99%
“…PKD1 floxed and PKD1-KO mice littermates brain vascular anatomy was analyzed as described 61 . Briefly, mice were anesthetized by an i.p.…”
Section: Methodsmentioning
confidence: 99%